ILEAL MUCOSAL EPITHELIAL CELL PROLIFERATION IN OLD AND MICE WITH ALZHEIMER’S DISEASE - Dinić, Jovana; Đorđević, Isidora; Vuković, David; Puškaš, Nela (Medicinski podmladak, 2025)
Introduction: The epithelial cell layer of the gastrointestinal tract undergoes constant renewal initiated by the proliferation of cells in the crypts of Lieberkühn. Changes in GIT function are often seen in elderly patients and patients with neurodegenerative diseases, such as Alzheimer’s disease. The proliferation rate of cells in the crypts of the small intestine has been shown to change with aging. Still, there are no studies investigating such changes in patients with Alzheimer’s in the available literature. Nuclear protein Ki-67 can be used as a reliable marker for monitoring cells in proliferation. The Aim: This study aimed to analyze the proliferation of epithelial cells in the crypts of the ileum of old mice, and in transgenic 5xFAD mice by monitoring the expression of Ki-67 protein. Material and Methods: Transgenic 5xFAD mice were used as a model of Alzheimer’s disease, and wild-type mice were used as a control group. The ileum was taken after sacrificing 8- and 36-week-old males. Visualization of Ki-67-positive cells in the crypts was demonstrated immunohistochemically, using antibodies to the Ki-67 protein. Measurements of the crypt’s perimeter and Ki-67-positive cells were evaluated on histological images at a total magnification of 400x using Leica Application Suite 4.4.0 software. The obtained values were analyzed using the ANOVA statistical test. Results: In the group of 8-week-old transgenic mice, a highly statistically significant perimeter decrease was shown compared to the control group. A highly statistically significant reduction in the number of Ki-67+ cells per 100 μm of the perimeter length was demonstrated in the group of 36-week-old transgenic mice compared to both the corresponding control group and younger transgenic animals. Conclusion: The results of this study indicate that the 5xFAD genotype significantly affects the perimeter of younger mice’s crypts, already at the moment of amyloid plaques accumulation in subiculum and deep cortical layers, and before the appearance of the first symptoms, while the proliferative capacity of the ileum epithelium has an effect only over a longer period, i.e. in older mice.